Energy-efficient wireless sensor network for real-time environmental monitoring: Simulink-based design - Fatai Olatunde Adunola; Victor Nnamdi Omeke; Ashraf Adam Ahmad; Asharimantun Reuben Bunu; Alfred John Nkohon; Emmanual Obiajulu (Discover Electronics)
Abstract This research focuses on designing an Energy-efficient Wireless Sensor Network for monitoring environmental parameters that tracks variables such as temperature, humidity, air quality, and noise levels in real time. The methodology includes modelling and simulating a wireless sensor network using Simulink, implementing a network that incorporates 4 separated sensor nodes that transmits to a gateway with a time lag of 6 min between each node, implementing a thresholding algorithm for energy efficiency, the network is programmed to transmit for 5 min every 4 h for a total period of 24 h. Simulation results showed energy reductions of up to 13.4% and battery life increases of up to 15.49% compared to traditional methods enabling the system to remain in the field for longer. This research is significant as it enhances the understanding of wireless sensor network applications in environmental monitoring. It aids informed decision-making for sustainability efforts and may support future developments in smart city initiatives and other related areas. This system’s efficiency, low power consumption, and scalability make it ideal for deployment in remote areas, providing a cost-effective framework for environmental monitoring with applications in smart cities, agriculture, and public health.